Liberating farming from the CAP - Séan Rickard (Institute of Economic Affairs (IEA), 2012)
Reforming the controversial policyExecutive summary:By 2020 the EU is planning to increase expenditure on the Common Agricultural Policy (CAP) by some exteuro8billion a year at a time of catastrophically bad public finances.Despite the concern about pressure on food prices, reform of the CAP will not increase efficiency or lower prices to the consumer.The sweeping rejection of the benefits of new technologies and the proposals for more government control of food markets by many NGOs and lobby groups would exacerbate current problems.The geographical and economic realities are such that yields per hectare will have to increase substantially over the next 40 years.The CAP - especially after recent reforms - leads to farm yields well below the level of maximum efficiency. This lack of efficiency has several dimensions: land is not used for the most efficient crops; yields per hectare are well below the maximum attainable levels; and incentives to adopt - or research - new technologies that will increase productivity have been blunted.Research shows that farm subsidies do not necessarily help bio-diversity and that their abolition would lead to a less than corresponding fall in farm incomes. To a large extent, subsidies become capitalised in land values, thus increasing costs to farmers. Between 1992 and 2009 - the period since the introduction of direct payments under the CAP - the value of agricultural land and buildings in the UK rose 400 per cent compared with 38 per cent general inflation. This suggests that one of the effects of removing direct payments would be a decline in land prices, rents and associated production costs.The abolition of subsidies in New Zealand demonstrates how government subsidies damage productivity and their removal leads to increased productivity.The EU has articulated an ambitious strategy for Europe that sees biotechnology as key in fighting hunger and malnutrition and feeding an increasing human population on the currently cultivated land area with reduced environmental impact. Yet, the EU has positioned itself at the extreme restrictive end of the regulatory continuum concerning GM products thereby effectively constraining research and reducing take-up - the EU is therefore holding back potentially far reaching changes in farm productivity growth and competitiveness.In addition to deregulating agricultural technology, the EU should also phase out direct payments to farmers amounting to exteuro40bn per year. This would dramatically reduce government expenditure as well as leading to a more efficient farming sector, higher productivity and lower food prices.The current review of the CAP represents the best opportunity for a complete change in agricultural policy that meets the challenge of rising global demand for food, but the reform must be radical.
Keywords: 330; EU agricultural policy; agricultural reform; impact analysis; EU countries; New Zealand; EU-Agrarpolitik; Agrarreform; Wirkungsanalyse; EU-Staaten; Neuseeland